Manual das atividades da auditoria interna da UFPB: contribuição à unidade de Auditoria da Universidade Federal da Paraíba - Almeida, Izabel Cristina Carvalho de (2019)
Given the convergence of international auditing standards and practices, translated by the Federal Accounting Council (CFC), the Federal Court of Accounts (TCU) and others disciplined by the Comptroller General of the Union (CGU), as well as the institutional rules of the University Federal da Paraíba (UFPB), which imposes adjustments to these new guidelines, coupled with the recent changes in 2018 in the UFPB Internal Audit unit (AUDIN / UFPB) and the absence of a document consolidating this information, led to the need to update knowledge improve the performance of the work performed by the internal audit professionals and standardize the audit unit documents. The objective of this research was to identify the necessary procedures to elaborate a manual of audit activities, in order to contribute to the improvement of the activities performed in the Internal Audit Unit of UFPB. This research was a qualitative, applied case study, where bibliographic research and documentary research were carried out. The final result will be the elaboration of a manual of Internal Audit activities, aiming to systematize the audit activities, as a way to guide the technical staff. AUDIN / UFPB, aiming its implementation in the audit sector of the Institution. As a result, this paper presents a Procedures Manual for the professional practice of AUDIN / UFPB activities, considering that the manuals are documents designed to standardize procedures, improve the flow of information between internal auditors and users, thus comprising the senior management (Councils and Rectory), the audited units, as well as the academic community and other stakeholders.